Developing Integrative Learning Model in Social Studies Education to Enhance Students Cultural Sensitivity at Junior High School - Mansyur, Alif Ilman; Supriatna, Nana; Sapriya; Komalasari, Kokom (Universitas Djuanda, 2026)
This study develops and validates a contextually grounded Integrative Learning model that effectively bridges global multicultural education frameworks with Indonesian local wisdom to enhance cultural sensitivity among junior high school students. in Lombok, West Nusa Tenggara. The research addresses the gap between multicultural education theory and practical implementation in diverse cultural contexts. Using Research and Development (R&D) methodology, this study encompasses three phases: preliminary study, development, and testing. Data were collected through observations, interviews, documentation, and questionnaires involving teachers and students from six schools in West Lombok. The preliminary findings indicate that current social studies instruction lacks integration of local cultural values and multicultural perspectives. The developed model incorporates Sasak local wisdom and employs Fogarty's curriculum integration framework, utilizing multiple integration patterns including connected, nested, sequenced, shared, and webbed approaches. Validation by experts and field testing demonstrate the model's feasibility. Pre-experimental design with one-group pretest-posttest was employed to measure effectiveness across three implementation sites: SMPN X (n=28), SMPN Y (n=26), and SMPN Z (n=31). Statistical analysis revealed significant improvements at all sites with paired samples t-tests showing p-values of 0.020, <0.001, and 0.010 respectively. Normalized Gain (N-Gain) analysis yielded consistent